Breakdown of the finite-time and -population scalings of the large deviation function in the large-size limit of a contact process. (29th August 2018) - Guevara Hidalgo, Esteban
Abstract: In a recent study (Nemoto et al 2017 Phys. Rev . E95 012102; Guevara Hidalgo et al 2017 Phys. Rev . E95 062134), the finite-time ( t ) and -population size ( N c ) scalings in the evaluation of a large deviation function (LDF) estimator were analyzed by means of the cloning algorithm. These scalings provide valuable information about the convergence of the LDF estimator in the infinite- t and infinite- N c limits. For the cases analyzed in that study, the scalings of the systematic errors of the estimator were found to behave as t −1 and in the large- t and large- N c asymptotics. Moreover, it was shown how this convergence speed can be used in order to extract an asymptotic limit which rendered a better LDF estimation in comparison to the standard estimator. However, the validity of these scaling laws, and thus the convergence of the estimator, was proved only in systems for which the number of sites L (where the dynamics occurs) was small. In this paper, the analysis is extended to a wider range of system sizes L . We show how the introduction of the exponents and allows us to characterize the behavior of the LDF estimator for any system size. From these generalized - and -scalings, we verify that in the large- L limit the t −1 - and -scalings are no longer valid. Moreover, as the convergence of the estimator relies on the positivity of these exponents, we show how for some cases can be negative implying that the estimation provided by the cloning algorithm is no longer reliable.